2008
DOI: 10.1074/jbc.m800264200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D-dependent Phosphorylation and Nuclear Export of Histone Deacetylase 5 Mediates Vascular Endothelial Growth Factor-induced Gene Expression and Angiogenesis

Abstract: Vascular endothelial growth factor (VEGF) is essential for normal and pathological angiogenesis. However, the signaling pathways linked to gene regulation in VEGF-induced angiogenesis are not fully understood. Here we demonstrate a critical role of protein kinase D (PKD) and histone deacetylase 5 (HDAC5) in VEGF-induced gene expression and angiogenesis. We found that VEGF stimulated HDAC5 phosphorylation and nuclear export in endothelial cells through a VEGF receptor 2-phospholipase C␥-protein kinase C-PKD-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
152
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(161 citation statements)
references
References 32 publications
4
152
3
2
Order By: Relevance
“…Nurr77 transcription is regulated by the MEF2 transcriptional factor and Ha et al, showed that MEF2 transcriptional activity was induced by VEGF. Furthermore, this induction was prevented by the overexpression of either a kinase dead PKD1 mutant or a constitutively active HDAC5 mutant (10). Nurr77 and another immediate-early gene, Egr3, are strongly and rapidly induced by VEGF in HUVECs (30), and PKD knockdown by siRNA reduced the VEGF-induced transcription of these genes, though Nurr77 transcription was only affected by PKD2 knockdown (31).…”
Section: Pkd Function In Endothelial Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nurr77 transcription is regulated by the MEF2 transcriptional factor and Ha et al, showed that MEF2 transcriptional activity was induced by VEGF. Furthermore, this induction was prevented by the overexpression of either a kinase dead PKD1 mutant or a constitutively active HDAC5 mutant (10). Nurr77 and another immediate-early gene, Egr3, are strongly and rapidly induced by VEGF in HUVECs (30), and PKD knockdown by siRNA reduced the VEGF-induced transcription of these genes, though Nurr77 transcription was only affected by PKD2 knockdown (31).…”
Section: Pkd Function In Endothelial Cellsmentioning
confidence: 99%
“…The reason for the discrepancy between our findings and those of Ha et al is unclear, but it is possible that overexpression of the kinase dead PKD1 mutant may have had an adverse effect on PKD2 activity. Both Egr3 and Nurr77 are required for effective VEGF-mediated migration and tube formation in HUVECs, suggesting that PKD may regulate angiogenic responses in part by mediating transcription of these genes (10,31). HDAC7 also regulates Nurr77 transcription via MEF2, and another gene, RCAN2, which stimulates angiogenesis via the calcineurin-NFAT pathway (29,32).…”
Section: Pkd Function In Endothelial Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, class IIa HDACs, such as HDAC5, acting as transcriptional repressors, have been implicated in cardiac hypertrophy, skeletal muscle differentiation, and angiogenesis (5)(6)(7)(8)(9)(10). Dynamic nucleocytoplasmic shuttling has been proposed as a fundamental mechanism regulating the function of class IIa HDACs (1,(11)(12)(13).…”
mentioning
confidence: 99%